The Influence of OHS Knowledge and Self-Regulation on OHS Compliance (RETRACTED) - Kurniati, Hafidha Tri; Fathiyah, Kartika Nur (GUIDENA: Jurnal Ilmu Pendidikan, Psikologi, Bimbingan dan Konseling, 2021)
Occupational Health and Safety (OHS) was the most important part of work activity to prevent work-related accidents. Work accidents caused by workers were motivated by the non-compliance of workers in their work. Compliance was a measure for a person to act so that unwanted things do not occur, such as work accidents. OHS Knowledge and self-regulation affected one's compliance to comply with OHS. The purpose of this research was to determine the influence did OHS knowledge (Occupational Health and Safety) and self-regulation had on the compliance of implementing OHS on students who are practicing in chemical laboratories. This research uses a quantitative approach with the research ex-post facto. The research sample used by the method was sampling accidental 80 chemistry students at Yogyakarta State University. The research data collection tools are a compliance questionnaire to apply OHS, self-regulation, and OHS knowledge. The data analysis technique used is the multiple linear regression test. The results showed an effect of OHS knowledge (Occupational Health and Safety) and self-regulation on compliance with applying OHS to students who practice in chemical laboratories (p = 0,000, F = 82,489) with an effective contribution of 68.1%.Keywords: OHS knowledge; self-regulation; compliance with applying OHS Keselamatan dan Kesehatan Kerja (K3) merupakan bagian terpenting dalam suatu aktivitas pekerjaan guna mencegah adanya kecelakaan akibat kerja. Kecelakaan kerja oleh pekerja dilatarbelakangi karena ketidakpatuhan pekerja dalam bekerja. Kepatuhan diketahui sebagai tolak ukur seseorang dalam bertindak agar tidak terjadi hal-hal yang tidak diinginkan seperti adanya kecelakaan kerja. Tujuan penelitian ini adalah untuk mengetahui adanya pengaruh pengetahuan K3 (Keselamatan dan Kesehatan Kerja) dan regulasi diri terhadap kepatuhan menerapkan K3 pada mahasiswa praktikan di laboratorium kimia. Penelitian ini menggunakan pendekatan kuantitatif dengan jenis penelitian ex-post facto. Sampel penelitian yang digunakan dengan metode sampling aksidental berjumlah 80 mahasiswa kimia di Universitas Negeri Yogyakarta. Alat pengumpulan data penelitian berupa kuesioner kepatuhan menerapkan K3, regulasi diri, dan pengetahuan K3. Teknik analisis data yang digunakan adalah uji regresi linier berganda. Hasil penelitian menunjukkan bahwa terdapat pengaruh pengetahuan K3 (Keselamatan dan Kesehatan Kerja) dan regulasi diri terhadap kepatuhan menerapkan K3 pada mahasiswa praktikan di laboratorium kimia (p = 0,000, F = 82,489) dengan kontribusi sumbangan efektif sebesar 68,1%.Kata kunci: pengetahuan K3; regulasi diri; kepatuhan menerapkan K3